Study on Fatigue Mechanism of Main Bearings of Shield Machine based on FRANC3D - Wei Chen; Jianxin Su (Jixie chuandong)
Taking the main bearing of the shield machine as the research object， and a finite element analysis on the contact fatigue mechanism of the main thrust raceway is carried out. Considering the size of the main bearing of the shield machine is too large， a simplified main thrust raceway contact model is used for finite element analysis， and the validity of the numerical model is verified by comparing the theoretical solution and numerical simulation solution of raceway contact stress. A semi-elliptical crack is inserted into the raceway surface based on FRANC3D to study the influence of load and friction coefficient on the fatigue damage of the main thrust raceway.